Actuator Development Step by Step: Pellet Particle Flux Control for Single- and Multiple-Source Systems. (2nd January 2022) - Lang, P. T.; Ploeckl, B.; Fischer, R.; Griener, M.; Kircher, M.; Kudlacek, O.; Phillips, G.; Sieglin, B.; Yamamoto, S.; Treutterer, W.; Team, AUG
Abstract: Fuel injection by means of solid cryogenic pellets is expected to provide a sound and efficient tool. Hence, the installation of a pellet launching system will be a necessity. Yet, pellets are considered as a serviceable actuator for integrated supplementary functions as, e.g., fast and efficient delivery of seeding gas, or in case needed, the pacing of edge-localized modes. Consequently, a control scheme has to be developed that is capable of mastering the simultaneous actuations covering different tasks. Our scheme relies on pellet launching by a centrifuge accelerator, providing the option for precisely predictable pellet injection sequences. In order to develop a suitable actuator control scheme, as a first step the central part was brought into service at ASDEX Upgrade. It proved operational for feedback particle flux control of a single pellet source. In a subsequent step, it is now upgraded to enable multitasked control of the JT-60SA multipellet source currently under construction. In its finally designated configuration, this control scheme provides a potential solution for a reactor-grade system.